(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the development of coping strategies as a decisive factor in forming professionally competent and psychologically resilient personnel within the internal affairs system. The study highlights key directions such as psychological training, development of reflection skills, stress management techniques, and enhancement of emotional intelligence.